2016
DOI: 10.1136/gutjnl-2016-313051
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Microscopic Colitis Disease Activity Index: a prospective cohort study

Abstract: The MCDAI strongly predicted the PGA and correlated with a validated measure of quality of life. Several symptoms in addition to diarrhoea are associated with disease severity in MC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
0
28
0
3
Order By: Relevance
“…Microscopic colitis (MC) is a chronic inflammatory bowel disease (IBD) with few or no endoscopic abnormalities (1)(2)(3). Patients with MC present chronic, non-bloody watery diarrhoea, however some may suffer from constipation, abdominal pain or even remain symptom free (4,5). Patients with MC are more often middle aged or older women in their seventh decade of life.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic colitis (MC) is a chronic inflammatory bowel disease (IBD) with few or no endoscopic abnormalities (1)(2)(3). Patients with MC present chronic, non-bloody watery diarrhoea, however some may suffer from constipation, abdominal pain or even remain symptom free (4,5). Patients with MC are more often middle aged or older women in their seventh decade of life.…”
Section: Introductionmentioning
confidence: 99%
“…5(10), 616-629 617 recent population-based studies is found in ~10-15% of patients with chronic watery diarrhea undergoing endoscopy with multiply biopsy (Rasmussen et al 2016) (Bonderup et al 2015) (Gentile et al 2014). MC is a benign condition that has been shown to severely impact health-related quality of life (HRQOL), with baseline HRQOL being lower than that of patients with ulcerative colitis, anal fissures, chronic constipation and faecal incontinence (Nyhlin et al 2014) (Cotter et al 2016). The natural history of MC varies considerably (Ingle 2014) (Villanacci et al 2016).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…The differential diagnosis of MC is very large and mainly includes infectious colitis, resolving acute infectious colitis, post-dysenteric IBS, drug-induced changes, particularly those related to the intake of non-steroidal inflammatory drugs, but the classic IBD and celiac disease also have to be ruled out ) (Guagnozzi et al 2016)(Jauregui-Amezaga, Vermeire, and Geboes 2016). Usually colonoscopy cannot be avoided in patients with chronic diarrhea, but the ability to identify a subset of patients at higher risk of MC has the potential to reduce the number of patients in whom biopsies are taken and recent scoring systems have been proposed to identify lower risk patients (Cotter et al 2016) (Kane et al 2015). Series of clinical studies have shown that those patients with MC are more than 50 years of age, report weight loss, have a duration of diarrhea < 12 months, have recently taken a new drug, and have a coexisting autoimmune disease(s) (Macaigne et al 2014) (Cotter et al 2016) (Kane et al 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations